1993
DOI: 10.1182/blood.v81.1.222.bloodjournal811222
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing human sickle hemoglobin are partially resistant to rodent malaria

Abstract: The polymorphic frequency of the gene for beta s-globin involved in the generation of sickle trait and sickle cell anemia in the human population is caused by the enhanced resistance of sickle trait individuals to Plasmodium falciparum malaria, as supported by epidemiologic and in vitro studies. However, the mechanism for the protective effect of sickle hemoglobin in vivo has not been fully defined. The generation of transgenic mice expressing high levels of human beta s- and alpha-chains has allowed us to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Examples include the apparent change in HEMP1 accessibility to antibody in thalassaemic red blood cells, which appears to make parasites more susceptible to clearance by immune mechanisms (Luzzi et al, 1991a,b). Transgenic mice with specific abnormalities of red blood cells have been examined for susceptibility to malaria infection (Shear, 1993;Shear et al, 1993Shear et al, , 1998Hood et al, 1996). In general, these studies have confirmed the importance of abnormal haemoglobin in restricting parasite growth.…”
Section: The Host-parasite Relationshipmentioning
confidence: 91%
“…Examples include the apparent change in HEMP1 accessibility to antibody in thalassaemic red blood cells, which appears to make parasites more susceptible to clearance by immune mechanisms (Luzzi et al, 1991a,b). Transgenic mice with specific abnormalities of red blood cells have been examined for susceptibility to malaria infection (Shear, 1993;Shear et al, 1993Shear et al, , 1998Hood et al, 1996). In general, these studies have confirmed the importance of abnormal haemoglobin in restricting parasite growth.…”
Section: The Host-parasite Relationshipmentioning
confidence: 91%
“…In particular, this approach enables the study of the role of the reticuloendothelial system in the recognition of infected erythrocytes under well-controlled experimental conditions. Important results have been already achieved by Shear et al (1993Shear et al ( , 1994, who observed that in transgenic p*S mice splenectomy reverses completely the protection against l? chabaudi adami infection.…”
Section: Current Understanding Ofmentioning
confidence: 97%
“…Also in the case of HbS, accelerated phagocytosis of infected erythrocytes would provide the most efficient level of protection. It has been in fact observed that splenectomy of P*S transgenic mice completely reverses the protection against Plasmodium chabaudi adami infection (Shear 1993;Shear et al, 1994). Furthermore, HbSS subjects, who have anatomical and functional asplenia, have no or reduced resistance against the infection (Luzzatto and Pinching, 1990).…”
Section: Protection Afforded By Dietary Intakes Of Oxidative Substancesmentioning
confidence: 99%
“…Choroid abnormalities were later confirmed in human autopsies (Fukushima et al , 1997). This model has been useful in the elucidation of the mechanisms of malaria protection afforded by the β S gene in vivo (Shear et al , 1993), particularly the important role of the spleen in this innate resistance. Osarogiagbon et al (1997) have provided in vivo evidence of oxidative stress in hypoxia‐exposed mice of this lineage.…”
mentioning
confidence: 99%